1995
DOI: 10.4319/lo.1995.40.4.0740
|View full text |Cite
|
Sign up to set email alerts
|

Mesocosm experiments quantify the effects of eutrophication on eelgrass, Zostera marina

Abstract: Outdoor mesocosm experiments were used to examine the response of eelgrass communities to excess nutrient loading and reduced light that simulated coastal eutrophication. A series of replicated manipulations conducted between 1988 and 1990 demonstrated the effects of reduced available light and increased loading of nitrogen plus phosphorus on habitats dominated by eelgrass Zostera marina L. Shade and nutrients each significantly affected eelgrass growth, morphology, density, and biomass. WC found no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
175
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(192 citation statements)
references
References 29 publications
14
175
1
2
Order By: Relevance
“…Several studies have demonstrated that leaf length increases with reduced light intensity but decreases with nutrient addition (e.g. Lee et al, 2007;Short et al, 1995). In our study increased nutrients did not significantly impact the leaf length of seagrasses, but this may have been due to nitrogen limiting growth (the low %N in the seagrass leaves).…”
Section: Slow Indicator Responses Of Seagrassescontrasting
confidence: 59%
“…Several studies have demonstrated that leaf length increases with reduced light intensity but decreases with nutrient addition (e.g. Lee et al, 2007;Short et al, 1995). In our study increased nutrients did not significantly impact the leaf length of seagrasses, but this may have been due to nitrogen limiting growth (the low %N in the seagrass leaves).…”
Section: Slow Indicator Responses Of Seagrassescontrasting
confidence: 59%
“…Light reduction caused decreased leaf, rhizome and root elongation rates, followed by diminished production. This phenomenon has been widely recorded in previous studies, independently of the nature of the screen used (Philippart 1995, Short & Burdick 1995, Longstaff & Denninson 1999, Moore & Wetzel 2000, Havens et al 2001, Nelson & Lee 2001, RuĂ­z & Romero 2001, Peralta et al 2002, Brun et al 2003a. Non-structural carbohydrates were mobilized, both in above-and belowground tissues, to meet carbon demands under light limitation (Alcoverro et al 1999, RuĂ­z & Romero 2001, Peralta et al 2002, Brun et al 2003a, with the capacity of sucrose formation and exportation restricted in aboveground tissues, and sink strength stimulated in belowground tissues, under low light (Brun et al 2003a).…”
Section: Discussionmentioning
confidence: 96%
“…Most of the studies on the effects of light reduction on seagrass survival and growth use neutral density screens to simulate such light conditions (Philippart 1995, Short et al 1995, Lee & Dunton 1997, Moore & Wetzel 2000, Peralta et al 2002. However, the major light-absorbing components (gilvin, tripton, phytoplankton and macroalgae) in the aquatic system are not optically neutral (Kirk 1983), which becomes evident under a dense blanket of ephemeral macroalgae.…”
Section: Zostera Noltii)mentioning
confidence: 99%
“…This explm~ation is most often p r o p o s e d to account for the ioss of seagrasses in North kanerica (Orth and Moore 1983; N e u n d o r f e r and Kemp 1993; Short et al 1995;Tomasko et al 1996), Europe (Giesen et al 1990;den Hartog 1994), and Australia (Cambridge and M c C o m b 1984;Shepherd et al 1989). An i m p o r t a n t point is that, for the most part, these studies were conducted in the absence of consumers.…”
Section: Seagras~ Meadowsmentioning
confidence: 99%